Sistema de gestión y reducción de accidentes laborales en la construcción de viviendas multifamiliares, 2019-2023 - Gutiérrez Hidalgo, Kathiuska Brigitte (2025)
The study presented here analyzes the association between the occupational health and safety management system (hereinafter SGSST) and thereduction of accidents in multifamily housing construction sites; because there is no research that addresses this problem specifically. The study isof an applied type, of a non-experimental design, the population is made up of 56 multi-family housing construction sites that have recorded 26 workaccidents in the period 2019 to 2023, it should be noted that all of them correspond to the construction stage, of which 19 accidents correspond to thestructural work - formwork substage, 4 accidents to the interior and exterior architecture substage, and 3 accidents to the structural work - constructionsubstage of the helmet.No sample was used because all the information was available. The technique used was documentary analysis and the instruments used were the checklist and the record of work accidents.The findings supported the proposed hypothesis, evidencing a statistically significant association between the variables analyzed, with a p-valueof 0.046; Based on the above, it is concluded that occupational health and safety management systems in multifamily projects have a significantrelationship with the reduction of work accidents.